Avaliação da estabilidade oxidativa de blendas de biodiesel de óleo de soja e de óleo de macaúba durante armazenamento - Oliveira, Romário de Lima (2016)
The growing production of biodiesel each year reflects the success of National Production and Use of Biodiesel Program, however the Brazilian biodiesel (about 80% is produced from soybean oil) is chemically unstable, requiring the use of antioxidant additives to improve the stability of biodiesel. Alternatively, the blends using biodiesels for the same objective, in that sense, this work was aimed at the study of biodiesel blends of behavior composed of soy biodiesel with macaúba oil biodiesel in varying proportions, free of antioxidant additives, during three months of storage. With respect to the use of macaúba oil biodiesel as enhancing the oxidative stability of soybean biodiesel, the results obtained by the Rancimat technique proved very promising, especially at time zero. However, after 30 days of storage of the biodiesel blends induction period fell dramatically. The viscosity parameters, density and filter plugging point the cold remained within the limits established by the ANP during the storage period.